Implementasi Kewajiban Pembinaan Terhadap Pidana Anak Di Lembaga Pembinaan Khusus Anak Pekanbaru Berdasarkan Undang-Undang Republik Indonesia Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak - Erpis Candra (Widya Yuridika, 2020)
In the Law of the Republic of Indonesia Number 11 of 2012 concerning the Criminal Justice System for Children 85 paragraph 2 and paragraph 3 states that it is mandatory to carry out coaching for children, both educational coaching, skills development, and personal development, but in reality the coaching obligations at LPKA have not running optimally, especially in skills development and education coaching. The education development in LPKA is non-formal education, which includes activities Package A for elementary schools (SD), Package B for junior high schools (SMP), and Package C for senior high schools (SMA). The method used is sociological legal research. Data sources consist of primary legal data, secondary legal data, and tertiary legal data. In this study the data were analyzed qualitatively and in drawing conclusions by thinking deductively. Based on the results of the research, it is known that the implementation of the Guidance Obligation of Criminal Children in the Pekanbaru Children Special Guidance Institution based on the Law of the Republic of Indonesia Number 11 of 2012 concerning the Criminal Justice System for children that fostering criminal children must have a program that must be able to humanize children, nurture, foster, guide children. criminal. The development of criminal children must be oriented to social values according to the author in accordance with the implementation of child protection. The Legal Consequences of the Implementation of Child Criminal Guidance Obligations at the Pekanbaru Children Special Guidance Institution based on the Law of the Republic of Indonesia Number 11 of 2012 concerning the Child Criminal Justice System that the treatment of child-friendly systems is applied such as mentoring, recognition of themselves and their environment, programs in the form of coaching , and care for correctional treatment to prepare for social reintegration of children. Correctional care can be done when the child is placed in the Special Child Development Institution (LPKA).